"Prinsip Etika Kristen dalam Bisnis UMKM di Era Digital: Studi terhadap Pelaku Usaha Kristen" - Kemur, Yunita; Barek, Titya Advianti P (Jurnal Ilmiah Wahana Pendidikan, 2025)
ABSTRACT This study aims to identify and analyze the application of Christian ethical principles in the business practices of Christian MSME (Micro, Small, and Medium Enterprises) actors in the digital era. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving entrepreneurs from various sectors, including culinary, beauty, fashion, and trade. The findings reveal that Christian MSME actors apply five core ethical principles in their business activities: love, justice, honesty, patience, and diligence. These principles are reflected in honest digital interactions, courteous customer service, and professional conduct. Despite facing internal and external challenges, the entrepreneurs consistently uphold integrity and utilize social media positively as a means of witnessing their faith. The results affirm that Christian ethics can serve as a strong foundation for building competitive, sustainable businesses that generate both spiritual and social impact in the midst of digital transformation.